GPS Logger Development Using an Atmega 2560 Microcontroller - Purwowibowo Purwowibowo; Sensus Wijonarko; Tatik Maftukhah (LIPI Press, Anggota IKAPI, 2019)
Although the applications of GPS navigation have been widely used, the implementations of GPS logger currently are still scarce. GPS loggers are able to keep locations in form of coordinates and UTC, so that the data might be accessed later on using SD cards equipped in the devices. The purpose of this research was to create a GPS logger using an open source microcontroller system to maintain flexibility in development. A Mega ADK Arduino board and a GPS shield Ublox Lae-6H ware used. Furthermore the device was provided with a Thin Film Transistor (TFT) display and a SD module. The received data ware displayed on the TFT in coordinates of latitude, longitude and altitude. To get the accuracy level, measurement results of the GPS logger was compared with measurement results from other GPS products in several places. According to the comparison, the average accuracy of the GPS logger was less than 2 meters.